(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Aqueous and ethanolic extracts obtained from Chrysophyllum albidum plant parts (leaves, roots, and seeds) were used to evaluate the potential antibacterial activity against bacteria isolated from urinary catheter tips. The following isolates were recovered: P. aeruginosa (7), S. aureus (15), E. coli (11), P. mirabilis (11), and K. aerogenes (6). The agar well diffusion method was used. The average percentages of antimicrobial resistance to gentamicin among the isolates were 45.5% for P. aeruginosa, 42.1% for E. coli, 46.9% for K. aerogenes, and ˃90% for the other isolates. The ethanolic extract mixtures (leaf, root, and seed) had the greatest effect on all the isolates, with inhibition zones (IZs) ranging from 8 to 26 mm and MICs ranging from <16 to 32 mg/mL. The Potencies of the C. albidum extracts based on the IZ and MIC values were greater in the extract mixtures, followed by those in the roots. Phytochemical screening revealed that all extracts contained phenols, except the seeds, while tannins were present in all extracts except the leaves. The activity of the ethanolic extracts of each part at both high and low concentrations was greater than that of the aqueous extracts at the same concentrations (p < 0.05). The acute toxicity results showed that the LD50 of the extracts was greater than 5000 mg/kg body weight, indicating no toxicity. The antibacterial activities of the extract mixtures and roots against the isolates confirmed the use of C. albidum in folk medicine for the treatment of catheter-associated urinary tract infections (CAUTIs), indicating its potential for use in novel antibiotic production.